Study on removal behavior and separation efficiency of naturally occurring bentonite for sulfate from water by continuous column and batch methods - Baker, Hutaf Mustafa; Ghanem, Raed Ahmad (European Journal of Chemistry, 2015)
The removal of sulfate using Jordanian bentonite has been investigated in this study. The surface of the bentonite was modified by calcinations at different temperature. The batch experiments of the equilibrium studies were carried out under different operating conditions. Kinetic modeling for the removal of sulfate ion was investigated using a pseudo-second-order, intraparticle diffusion and Elovich kinetic models to predict the rate constants and equilibrium capacities for this process using column reactor. It was found that intraparticle diffusion of the sulfate ion is the rate limiting step and played an important role in the mechanism of sulfate ion adsorption depending on the obtained activation energy, which was 32.8 kJ/mol. Also, the sorption isotherm analyzed using both the Langmuir and Freundlich models as a function of temperature. The isothermal data found to be fitted Langmuir model rather than Freundlich model. The positive value of ΔH (15.2 kJ/mol) indicated that the adsorption of sulfate ions on the adsorbent was an endothermic process and the positive value of ΔS (22.1 J/mol.K) indicated that the adsorption is favorable with small positive value of the free energy (ΔG).